Impending challenges of the burden of end‐stage kidney disease in Australia. Issue 8 (8th October 2019) - Lim, Wai H; Johnson, David W; McDonald, Stephen P; Hawley, Carmel; Clayton, Philip A; Jose, Matthew D; Wong, Germaine
Summary: Sex and age‐specific incidence rates of patients with treated end‐stage kidney disease (ESKD) in Australia are comparable to those in European countries, but substantially lower compared with those in the United States, Canada and many Asian countries. The incidence rates of treated ESKD in Australia increase with advancing age; however, the incidence of ESKD is likely to be underestimated because a proportion of patients with ESKD (about 50%) remain untreated. Late referral to nephrologists has reduced over the past decade, temporally associated with improved ESKD recognition. However, late referral still occurs in one in five Australians with ESKD. One in two Australians with ESKD has diabetes, with up to 35% of cases directly attributed to diabetes. Mortality rates for patients with ESKD remain substantially higher compared with the age‐matched general population, although there has been a significant improvement in survival over time. Cardiovascular disease and cancer are the two most common causes of death in patients with ESKD.